2016
DOI: 10.1016/j.clim.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 deficiency protects from lupus-like autoimmunity in the chronic graft-versus-host disease model of systemic lupus erythematosus

Abstract: MicroRNAs (miRNAs) are small, non-coding RNAs that regulate gene expression primarily at the post-transcriptional level. Emerging evidence supports a regulatory role for miRNAs in the immune response and autoimmunity. In this work, we investigated the implication of miR-21 in the experimentally inducible bm12→B6 cGVHD model of systemic lupus erythematosus (SLE). cGVHD host mice deficient in miR-21 show a 2-fold reduction in splenomegaly, significantly reduced autoantibody titers and down-regulated components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Therefore, the pleotropic effects of estrogen could promote immune activation both by upregulating TLR8 and the in vivo -generated ligand. Considering the strong association of dysregulated miR expression in SLE [11] and that miR-21 deficiency has been shown to protect from lupus-like autoimmunity in a mouse model [49], targeting miR-21 and any additional miRs potentially functioning as TLR ligands represents a novel therapeutic strategy to suppress inflammation in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pleotropic effects of estrogen could promote immune activation both by upregulating TLR8 and the in vivo -generated ligand. Considering the strong association of dysregulated miR expression in SLE [11] and that miR-21 deficiency has been shown to protect from lupus-like autoimmunity in a mouse model [49], targeting miR-21 and any additional miRs potentially functioning as TLR ligands represents a novel therapeutic strategy to suppress inflammation in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 contributes to aberrant CD4 + T cell responses in human SLE by targeting PDCD4, while inhibiting miR-21 in vitro improves abnormal CD4 + T cell responses, including the production of IL-10, and the expression of CD40L, as well as the capability to support B cell development, which indicates the pathogenic role of miR-21 in SLE (113). Garchow et al (114) reported that miR-21 deficiency protects mice from chronic graft-versus-host disease (cGVHD)-induced lupus by regulating Th17/Treg balance. They observed that cGVHD-affected mice with miR-21 deficiency have a reduced proportion of Th17 cells and an expanded compartment of Treg cells.…”
Section: Ncrnas Regulate the Aberrant Differentiation Of Cd4 + T Subsmentioning
confidence: 99%
“…They observed that cGVHD-affected mice with miR-21 deficiency have a reduced proportion of Th17 cells and an expanded compartment of Treg cells. Moreover, miR-21 inhibits the CD40: CD40L and CD28: CD80/86 co-stimulation pathways that are involved in establishing T cell tolerance and limiting adaptive immune response (114). Silencing miR-21 with a tiny seed-targeting LNA alleviates splenomegaly in B6.Sle123 mice and decreases the expression of PDCD4 and the population of Fas receptorexpressing lymphocytes (115).…”
Section: Ncrnas Regulate the Aberrant Differentiation Of Cd4 + T Subsmentioning
confidence: 99%
“…In another model of autoimmune disease, the EAE model of multiple sclerosis, targeting miR-21 using antisense was shown to block Th17 mediated inflammation leading to reduced disease burden (14). In mouse models of SLE, both targeting of miR-21 by antisense and miR-21 deletion decreased Th17 cells with a consequent increase in Tregs, conferring protection against disease (19,20). These results confirm that the miR-21/Treg axis is active in disease and confirmation of the results in the Li et al study using similar tools for vascular disease are forthcoming.…”
mentioning
confidence: 99%